Marine aquaculture in the pacific coast of Costa Rica: Identifying the optimum areas for a sustainable development - Calleja Apéstegui, Felipe (2022)
Sustainable marine aquaculture requires the definition of adequate areas for its development, where the productive activity has a lower impact on the environment and avoid conflicts with other coastal activities. The aim of this research is to identify the potential areas for marine aquaculture operations in the central and northern Pacific coast of Costa Rica, considering five fish species of commercial interest and three operation scale scenarios (large, medium and small scale). The mapping procedure considers the biological suitability for the species to have an optimum development, the structural suitability for the fish cages to endure the environmental conditions (mainly waves and currents), and the operational suitability for operation and maintenance activities associated to the fish production (e.g. feeding, harvesting, maintenance). Sea surface temperature, salinity, water clarity, wind speed and currents in open coasts regions were obtained from global models and satellite data. Currents and wave data in the Gulf of Nicoya, one of the main estuaries of the country, were modeled numerically. Available docking sites, marine protected areas and tourism sites were used and obtained from the corresponding national official entities. Results show a high potential for marine aquaculture projects, specifically for large and medium scale operations. Three out of five study species present high suitability in most of the study site, and the other two species present promising results in the Gulf of Nicoya. Small scale operations have several areas with high suitability for marine aquaculture projects, with extensions ranging from 101 km2 to 2 118 km2 depending on the species. At a regional scale, the Pacific coast of Costa Rica presents high potential for fish aquaculture, being a promising development medium for coastal communities as long as it is environmentally sustainable and compatible with other coastal activities such as tourism.